Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Design, synthesis and biological evaluation of novel azaspiro analogs of linezolid as antibacterial and antitubercular agents - Gadekar, Pradip K.; Roychowdhury, Abhijit; Kharkar, Prashant S.; Khedkar, Vijay M.; Arkile, Manisha A.; Manek, Hardik; Sarkar, Dhiman; Sharma, Rajiv; Vijayakumar, V.; Sarveswari, S. (European Journal of Medicinal Chemistry, 2016)
The design, synthesis and antimicrobial evaluation of a novel series of azaspiro analogues of linezolid (1) have been described. Linezolid comprises of a morpholine ring which is known for its metabolism related liabilities. Therefore, the key modification made in the linezolid structure was the replacement of morpholine moiety with its bioisostere, 2-oxa-6-azaspiro[3.3]heptane. Furthermore, the replacement of N-acetyl terminal of 1 with various aromatic or aliphatic functionalities was carried out. The title compounds were evaluated against a panel of Gram-positive and Gram-negative bacteria and Mycobacterium tuberculosis. Subsequent structure-activity relationship (SAR) studies identified several compounds with mixed antibacterial and antitubercular profiles. Compound 22 (IC50 0.72, 0.51, 0.88, 0.49 mu g/mL for Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis, respectively) exhibited similar antibacterial profile as I. The N-acetyl derivative 18 was similar to 1 in antitubercular profile. Thus, the present study successfully demonstrated the use of azaspiro substructure in the medicinal chemistry of antibacterial and antitubercular agents. (C) 2016 Elsevier Masson SAS. All rights reserved.

Design, synthesis, and biological evaluation of novel fluorinated pyrazole encompassing pyridyl 1,3,4-oxadiazole motifs - Desai, Nisheeth C.; Kotadiya, Ghanshyam M.; Trivedi, Amit R.; Khedkar, Vijay M.; Jha, Prakash C. (Medicinal Chemistry Research, 2016)
A rational approach was adopted for the synthesis of 1-(2-(3-(4-fluorophenyl)-1-phenyl-1H-pyrazol-4-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)prop-2-en-1-ones (5a-n) using conventional heating as well as microwave irradiation techniques. Compounds 5a-n were tested for their in vitro antimicrobial activity and cytotoxicity. Compounds 5g showed most potent antibacterial activity, while compound 5k emerged as the most effective antifungal agent. The most active compounds 5f, 5g, 5l, and 5m were also screened against methicillin-resistant Staphylococcus aureus. Among these compounds, 5g and 5m inhibited the growth against MRSA at low level of cytotoxicity. A binary quantitative structure-activity relationship based recursive partitioning model was developed to probe the physico-chemical properties influencing the structure-activity relationship for this class of molecules, which was used to correctly classify active and inactive compounds.

Design, synthesis and biological evaluation of (E)-5-styryl-1,2,4-oxadiazoles as anti-tubercular agents - Upare, Abhay Atmaram; Gadekar, Pradip K.; Sivaramakrishnan, H.; Naik, Nishigandha; Khedkar, Vijay M.; Sarkar, Dhiman; Choudhari, Amit; Roopan, S. Mohana (Bioorganic Chemistry, 2019)
Cinnamic acid and its derivatives are known for anti-tubercular activity. The present study reports the synthesis of cinnamic acid derivatives via bioisosteric replacement of terminal carboxylic acid with ``oxadiazole''. A series of cinnamic acid derivatives (styryl oxadiazoles) were designed and synthesized in good yields by reaction of substituted cinnamic acids (2, 15a-15s) with amidoximes. The synthesized styryl oxadiazoles were evaluated in vitro for anti-tubercular activity against Mycobacterium tuberculosis (Mtb) H37Ra strain. The structure-activity relationship (SAR) study has identified several compounds with mixed anti-tubercular profiles. The compound 32 displayed potent anti-tubercular activity (IC50= 0.045 mu g/mL). Molecular docking studies on mycobacterial enoyl-ACP reductase enzyme corroborated well with the experimental findings providing a platform for structure based hit-to-lead development.
Keywords: 1; 2; 4-Oxadiazole; Anti-tubercular; Bioisosteres; Cinnamic acid; Molecular docking

[DBUH][OAc]-catalyzed domino synthesis of novel benzimidazole incorporated 3,5-Bis (Arylidene)-4-piperidones as potential antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
A series of new benzimidazole incorporated 3,5-bis (arylidene)-4-piperidones were synthesized by using aryl aldehydes, piperidinone, 2-(chloromethyl)-benzimidazole and DBU acetate [DBUH][OAc] act as a catalyst under solvent free condition in excellent yields. The synthesized compounds were screened for their in vitro antimycobacterial activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. The compounds 4a, 4b, 4e, 4i, 4k and 4l are highly potent against both the strains. Most of the active compounds are non-cytotoxic against MCF-7, A549, HCT 116 and THP-1 cell lines. Furthermore, a molecular docking study of these compounds was carried out to investigate their binding pattern with the target, active site of mycobacterial enoyl-acyl carrier protein reductase (Inh A). Therefore, these compounds can be subjected for further optimization and drug development which could give promising chemical leads for treatment of TB.
Keywords: Antitubercular activity; curcumin; Cytotoxicity; Ionic liquid; multicomponent reactions

Design, synthesis of anticancer and anti-inflammatory 4-(1-methyl-1H-indol-3-yl)-6-(methylthio) pyrimidine-5-carbonitriles - Bhale, Pravin S.; Chavan, V. Hemant; Shringare, Sadanand N.; Khedkar, Vijay M.; Tigote, Radhakrishna M.; Mali, Nikita N.; Jadhav, Tukaram D.; Kamble, Nitin B.; Kolat, Swati P.; Bandgar, Babasaheb P.; Patil, Harshal S. (Synthetic Communications, 2022)
A novel series of 4-(1-methyl-1H-indol-3-yl)-6-(methylthio) pyrimidine-5-carbonitriles (4a-i) was synthesized and evaluated for anticancer potential against cell lines for breast cancer. Compounds 4b, 4e, and 4h exhibited prominent cytotoxicity against human breast carcinoma MCF-7 cell line with GI(50 )of 2.0, 0.5, and 0.5 mu M, respectively. Molecular docking study against EGFR tyrosine kinase could provide valuable insights into the plausible mechanism of action. The compounds could bind with significantly high binding affinity and their binding affinity scores could correlate well with the observed anticancer activity. Furthermore, compounds 4a, 4c, 4e, 4g, and 4i exhibited significant inflammatory activities as well which could expand the therapeutic domain of this novel series.
Keywords: Anti-inflammatory; Anticancer; Antioxidant; Indole; pyrimidine

[DBUH][HSO4]-catalyzed solvent-free synthesis of 1,5-benzodiazepine derivatives: bioevaluation and in silico molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Current Organic Chemistry, 2025)
Here, we report the solvent-free one-pot multicomponent synthesis of 4-substituted-1,5-benzodiazepine derivatives from O-phenylenediamine, aromatic aldehydes, and dimedone using [DBUH][HSO4] as a catalyst in excellent yields. This process was carried out in search of a reusable, easily accessible, affordable, and efficient catalyst. 1,5-Benzodiazepines demonstrate a new family of good inhibitors with potent anti-mycobacterial properties. The most promising compounds in the present series are 4c, 4i, and 4l which showed excellent activity and inhibited the growth of both MTB H37Ra and M. bovis BCG strains with lower MICs. The most active compounds were further studied for their cytotoxicity against cell lines MCF-7, A549, HCT116, and THP-1 by MTT assays and the compounds were found to be non-toxic. The fact that none of these compounds work against either Gram-positive or Gram-negative bacteria suggests that they are only effective against MTB. The in silico docking of the molecules against mycobacterial enoyl reductase, InhA enzyme could provide well-clustered solutions and have given valuable insights into the thermodynamic elements governing the binding affinities. The findings of this investigation unmistakably point to the discovery of extremely specific and selective MTB inhibitors, which can now be investigated further in search of possible anti-tubercular drugs.
Keywords: 1; 5-benzodiazepine; Antitubercular activity; Molecular docking; multicomponent reactions; [DBUH][HSO4]